The Pharmacogenetics Research Network: From SNP Discovery to Clinical Drug Response - Kathleen M. Giacomini; Christopher M. A. Brett; Russ B. Altman; N L Benowitz; M. Eileen Dolan; David A. Flockhart; J. A. Johnson; Daniel F. Hayes; Teri E. Klein; Ronald M. Krauss; Deanna L. Kroetz; Howard L. McLeod; et al. (2007)
The NIH Pharmacogenetics Research Network (PGRN) is a collaborative group of investigators with a wide range of research interests, but all attempting to correlate drug response with genetic variation. Several research groups concentrate on drugs used to treat specific medical disorders (asthma, depression, cardiovascular disease, addiction of nicotine, and cancer), whereas others are focused on specific groups of proteins that interact with drugs (membrane transporters and phase II drug-metabolizing enzymes). The diverse scientific information is stored and annotated in a publicly accessible knowledge base, the Pharmacogenetics and Pharmacogenomics Knowledge base (PharmGKB). This report highlights selected achievements and scientific approaches as well as hypotheses about future directions of each of the groups within the PGRN. Seven major topics are included: informatics (PharmGKB), cardiovascular, pulmonary, addiction, cancer, transport, and metabolism. Clinical Pharmacology & Therapeutics (2007) 81, 328–345. doi:10.1038/sj.clpt.6100087